ANALYSIS GRAMMATICAL EQUIVALENCE OF THE INDONESIAN TRANSLATION OF NARRATIVE THE SECRET GARDEN 56 MINUTES THROUGH YOUTUBE - Hisasmaria Hisasmaria; Pratiwi Samad (Universitas Islam Darul Ulum Lamongan, 2022)
The study aims to identify grammatical equivalence which covers number, gender, person, tense and aspect, and voice, to find out whether the translated sentence can be accepted in Indonesian structure and translation problems in English-Indonesian sentences. The data were taken from the film script “The Secret Garden 56 Minutes” in English and its Indonesian subtitles. This study was conducted based on qualitative research methods with the descriptive analysis. The results of this analysis show that there is grammatical equivalence which is found in the subtitles. They are categorized into number, person, gender, tense and aspect, and voice. The first, the grammatical equivalence in number included the singular or plural nouns in the source language (SL) can be translated into the singular or plural nouns in the target language (TL). Second, with regard to person and gender, source language (SL) personal pronouns can be translated into their respective pairs in the target language (TL), Third, tense and aspects, source language (SL) can be translated lexically or understood from the context. The four, voices the active form in the source language (SL) can be translated into the target language (TL) in an active or passive form, and the passive form is translated into a passive form. In translation, when a message or information is omitted by changing the form of the sentence, it will cause problems as in the film the secret garden 56 minutes.